Former Yugoslav Republic of Macedonia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
The economy of the Former Yugoslav Republic of Macedonia suffered a setback owing to the Kosovo crisis. The impact of the crisis, however, was less severe. Inflation remained low, the balance-of-payments position and the fiscal situation improved, and indicators of external vulnerability remained satisfactory. The National Bank of Macedonia faced contrasting challenges in the conduct of monetary policy. The pace of structural reforms picked up and a value-added tax was introduced. However, structural weaknesses in the financial system have prevented a more vigorous economic recovery.